AMELIORATIVE ACTION OF SYNTHETIC AND HERBAL ANTIOXIDANTS ON LEAD INDUCED HEPATOTOXICITY: AN IN VITRO STUDY - Shah, Flora C; K Jain, Nayan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: A lead is one of the most hazardous and persistent environmental toxicants of global concern today. The lead has propensity to act as a potent mammalian systemic toxicant. Therefore, investigation of effective ameliorative techniques against lead toxicity through proper exploration of molecular mechanisms is the main objective of the current study. Methods: Present in vitro study deals with the investigation of ameliorative effect of specific synthetic antioxidants in a mixture especially, N-acetyl cysteine (5.5 mM/kg/day), ascorbic acid (200 mg/kg/day), tocopheryl acetate (160 mg/kg/day), and thiamine (30 mg/kg/day) as novel combinational therapy approach as well as Bacopa monnieri (10 mg/kg/day) as herbal antioxidant therapy against lead induced hepatotoxicity. The current synergistic study involves culturing of goat liver in Dulbecco’s Modified Eagle Medium:F12 (1:1 mixture) culture media containing 1 ppm lead acetate along with co-administration of selective antioxidants at prescribed dosage for 6 hrs. Selective biochemical parameters such as lipid peroxidation (LPO), protein levels, alkaline phosphatase (ALPase), acid phosphatase (ACPase), succinate dehydrogenase (SDH), adenosine triphosphatase (ATPase), and superoxide dismutase (SOD) activities were analyzed and observed for protection against lead intoxication. Results: Results indicate significant alterations in all biochemical parameters studied in lead exposed cultures as compared to control. Total and soluble proteins, ALPase, SDH, and ATPase showed significant reduction while LPO, ACPase, and SOD activities increased significantly in lead exposed cultures as compared to control. The results also emphasized that simultaneous administration of prescribed antioxidants and lead in cultures manifested maintenance of all biochemical parameters studied nearest to control group. Conclusion: Synthetic and herbal antioxidants therapy have protective role against lead induced hepatotoxicity. Keywords: Lead toxicity, Synthetic antioxidants, Herbal antioxidant, Bacopa monnieri extract, Hepatotoxicity, Oxidative stress, Plumbism, Hepatoprotective activity, Lipid peroxidation, Superoxide dismutase.